Nanotechnologies - Wautelet, M. (IET circuits, devices and systems series, 2009)
The book reviews developments in the following fields: the nanotechnology revolution; atomic structure and cohesion; electronic structures of nanosystems; molecular electronics; neuroelectronics; plastic electronics; fabrication of nanostructures; organic-matrix-based nanocomposites; nanomagnetism; and nanotechnologies in perspective.